2018
DOI: 10.1177/1403494817743903
|View full text |Cite
|
Sign up to set email alerts
|

Concerns and future challenges of health literacy in the Nordic countries – From the point of view of health promotion practitioners and researchers

Abstract: There is a need for further studies providing a more in-depth understanding of the health literacy concept, knowledge on how to measure health literacy, ethical aspects, application in intersectoral collaboration as well as the adaptation to new technologies for information and communication in education supporting health literacy. As health literacy is an essential social health determinant, a concern and a future challenge must be, to make the health literacy concept familiar and visible in health promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…As Yu et al 57 describe, consideration of context is important and social and economic factors will vary across regions. It has been recognized that HL is a concept that is closely related to learning and education, it has been described as a key determinant of health 58 . This provides justification for a school‐wide approach, which includes co‐design and needs assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Yu et al 57 describe, consideration of context is important and social and economic factors will vary across regions. It has been recognized that HL is a concept that is closely related to learning and education, it has been described as a key determinant of health 58 . This provides justification for a school‐wide approach, which includes co‐design and needs assessment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that HL is a concept that is closely related to learning and education, it has been described as a key determinant of health. 58 This provides justification for a school-wide approach, which includes co-design and needs assessment. Action plans are a useful way to operationalize the stakeholder voices (parents, children, teachers, and local community) in the development of HL programs for children in schools.…”
Section: School Health Literacy Program Designmentioning
confidence: 99%
“…Ringsberg et al (111) raise some concerns for the future regarding HL in the Nordic countries, and one of the first centers on the conceptualization of HL. How we choose to define HL will have profound impact on the health care system and its users.…”
Section: How Do We Study Health Literacy?mentioning
confidence: 99%
“…According to Mancuso (2011), overcoming health literacy barriers to integrate beliefs, values, social and cultural traditions with information related to health can be done based on an individual’s personal orientation of the world to make informed decisions and change health-related behaviour. This can be compared with Olander, Ringsberg, and Tillgren’s (2014) description of health literacy as a competence useful in everyday life to promote and maintain good health across a lifetime. Equally, health literacy as a competence useful in everyday life is found in the four sub-themes in the findings of this study: Sharing relationships , playing to heal , being strong or frail and supporting the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that “both conceptualizations are important and are helping to stimulate a more sophisticated understanding of the process of health communication in both clinical and community settings, as well as highlighting factors impacting on its effectiveness” (p. 2072). Similar to viewing health literacy as an asset, Ringsberg, Olander, and Tillgren (2014) explained that it can be looked upon as a competence useful in everyday life to promote and maintain good health across a lifetime. According to Firman and Russel (1994), human beings’ life journey includes all the past hidden ages that impact human lives—this is a phenomenon they describe as the inner child.…”
Section: Introductionmentioning
confidence: 99%